Administracyjno-prawna problematyka zmiany nazewnictwa ulic Wrocławia w latach 1945–1946 - Jankowska, Marta (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2013)
This article discusses the issue of changing street names in post-war Wroclaw in the period from May 1945 to May 1946. Changes in terminology are analysed in the light of historical events and political turmoil taking place immediately after the liberation of Wroclaw. The article highlights the crucial role of the former administrative apparatus, which faced a serious challenge of restoring broad-based governance. The study emphasizes existing publications that describe change in the street names in Wroclaw and recognizes the deficiency of publications on administrative aspects in this regard. The article also examines the contemporary legal environment, which was the basis for the subsequent process of street name changes and its interpretation. Furthermore, this publication is a description of the first legislative acts of the street name changes as well as trends that emerged during the process.
Keywords: historia prawa; prawo publiczne; prawo prywatne; teoria prawa